Evaluation and Comparison of Charcot’s Triad and Tokyo Guidelines for the Diagnosis of Acute Cholangitis - Dinc, Tolga (Indian J Surg, 2016)
Reliability of Charcot’s triad has long been questioned. Tokyo Guidelines committee published Tokyo Guidelines in 2007 and 2013. The aim of this study was to retrospectively examine the patients who had been treated with the diagnosis of acute cholangitis and evaluate 2007–2013 Tokyo criteria and Charcot’s triad. The files of the patients with acute cholangitis in a referral center were examined retrospectively. All patients were classified and evaluated according to 2007 and 2013 Tokyo criteria and Charcot’s triad; and results were compared. It was detected that 51.7 % of patients who did not meet Charcot’s triad were in definitive diagnosis group of both Tokyo criteria. Kappa value was calculated as 0.404 in the analysis of consistency between two Tokyo criteria. Two patients who had features sufficient to objectively make the diagnosis of acute cholangitis failed to meet the Tokyo criteria 2007 or 2013. Charcot’s triad is not sensitive and specific enough in the diagnosis of acute cholangitis. Revision of Tokyo 2007 criteria caused a change in the diagnostic status of 15 % of the patients. It is remarkable that kappa value can hardly be considered as a sign of moderate agreement between two Tokyo guidelines. Tokyo criteria should be supported and updated.